Instruments to measure the inpatient hospital experience: A literature review - Kelly Edwards (The Beryl Institute, 2015)
Healthcare professionals worldwide are increasingly broadening their focus to include the experiences of patients and their family members as a means of assessing quality patient centered care. This paper seeks to identify and discuss instruments specifically designed to measure the inpatient hospital experience. A literature search focusing on pre-identified instruments as per the Health Foundation’s Helping Measuring Patient Centered Care database of measurement instruments (de Silva, 2014) and additional health databases (CINAHL, ERIC, EBSCO, HaPI, MEDLINE, PubMed and Psych INFO) was undertaken. Thirteen relevant instruments and seventeen associated studies (regarding instrument development and or validation) were identified. These instruments provide generalizable but less descriptive experience data, are predominantly based on post hospital discharge data and do not have identified feedback to staff mechanisms. Further research is warranted to co-develop an inpatient hospital experience instrument, designed to capture real time descriptive data with a corresponding feedback process to frontline clinicians. Ideally such an instrument could be designed using a participatory research methodology, whereby patients, friends, family and healthcare clinicians are equal co-developers.